2007
DOI: 10.1063/1.2751593
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of nanocrystalline Zn1−xMnxO

Abstract: The multi phonon Raman scattering in Mn doped (1%–10%) ZnO was observed at room temperature using 514.5nm Ar+ laser. The additional optical modes at 327, 332, 482, 532, and 680cm−1 in Zn1−xMnxO targets were identified as the second order Raman modes in the disordered lattice and the precipitation of the secondary phase ZnMn2O4. The crystalline grain sizes of 1%, 3%, 5%, and 10% Mn doped ZnO samples were calculated by phonon confinement model as 31.8, 18.3, 15.9, and 14.1nm, respectively. The optical band gap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 18 publications
6
87
1
Order By: Relevance
“…Figure 4 shows UV-Visible spectra of Zn 1-x Ni x O (x= 0.0, 0.02, 0.04, 0.06) nanocomposites annealed at 400 o C. Pure ZnO sample shows absorption band edge at 360 nm and observed band edge shows a shift towards higher wavelength side for the nickel doped sample i.e., at 320, 310 and 250 nm. The blue shift of the band edge for the nickel doped sample clearly indicates that Ni 2+ ions are incorporated into the ZnO lattice [29][30][31] which confirms the results of XRD and FTIR results. Optical band gap was evaluated using the equation: (αhν) n = A(hν-E g ) (11) Where α=absorption coefficient, hν=photon energy, A=constant relative to the material and n=2 for direct band gap material or ½ for an indirect band gap material.…”
Section: Xrd Studysupporting
confidence: 75%
“…Figure 4 shows UV-Visible spectra of Zn 1-x Ni x O (x= 0.0, 0.02, 0.04, 0.06) nanocomposites annealed at 400 o C. Pure ZnO sample shows absorption band edge at 360 nm and observed band edge shows a shift towards higher wavelength side for the nickel doped sample i.e., at 320, 310 and 250 nm. The blue shift of the band edge for the nickel doped sample clearly indicates that Ni 2+ ions are incorporated into the ZnO lattice [29][30][31] which confirms the results of XRD and FTIR results. Optical band gap was evaluated using the equation: (αhν) n = A(hν-E g ) (11) Where α=absorption coefficient, hν=photon energy, A=constant relative to the material and n=2 for direct band gap material or ½ for an indirect band gap material.…”
Section: Xrd Studysupporting
confidence: 75%
“…Therefore, the appearance of the peak at ß523 cm -1 could be used to characterize Mn 2+ doped into ZnO lattice as had been suggested by Zhu et al 53 Moreover, the intensity of the peak at 528 cm −1 is increased with increasing dose of Mn and begins to increase quickly when the dose of Mn is increased. Samanta et al 54 also observed the same.…”
Section: Raman Studiessupporting
confidence: 68%
“…Similar ob- servation of enhancement of the band gap of ZnO with Mn 2+ ion concentration was also made earlier by Mandal and Nath and Fukumura et al [26,27]. The crystalline grain sizes of 1%, 3%, 5%, and 10% Mn doped ZnO samples were calculated by the phonon confinement model as 31.8, 18.3, 15.9, and 14.1 nm, respectively by Samanta et al [28]. The group found that the optical band gap increased from 3.27-3.41 eV due to the Mn doping.…”
Section: Transmission and Absorbancementioning
confidence: 77%